2018
DOI: 10.1177/0192623318763586
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Characterization of Mifepristone-induced Ovarian Toxicity in Cynomolgus Monkeys

Abstract: Mifepristone, which is an orally active synthetic steroid with antiprogesterone activity, is known as an ovarian toxicant. Because the available data regarding the histopathologic characteristics of ovarian toxicity in nonhuman primates are limited, the present study was undertaken in order to investigate detailed histopathologic changes accompanying mifepristone-induced ovarian toxicity and its relationship to changes in menstrual cycle and circulating sex steroid hormone. Twenty mg/kg of mifepristone was ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We found no statistically significant differences in FSH, LH, and E2 levels between groups for the 12-week treatment. Recently, the effects of selective progesterone receptor modulators on endometrial thickness and endometrial changes associated with progesterone receptor modulators have attracted much attention but remain controversial . Our study showed that endometrial thickness detected by ultrasonography after mifepristone treatment was thinner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no statistically significant differences in FSH, LH, and E2 levels between groups for the 12-week treatment. Recently, the effects of selective progesterone receptor modulators on endometrial thickness and endometrial changes associated with progesterone receptor modulators have attracted much attention but remain controversial . Our study showed that endometrial thickness detected by ultrasonography after mifepristone treatment was thinner.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of selective progesterone receptor modulators on endometrial thickness and endometrial changes associated with progesterone receptor modulators have attracted much attention but remain controversial. [34][35][36] Our study showed that endometrial thickness detected by ultrasonography after mifepristone treatment was thinner. a Safety population was defined as the participants with at least 1 dose of the intervention or placebo drug.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and characteristics of corpora lutea are also important. Detailed descriptions of the histomorphology of the ovary throughout the ovarian cycle have been published with a luteinized regressive corpus luteum in the early follicular phase, a dominant large antral follicle in the late follicular phase and various stages of small, growing, antral, and atretic follicles and an old corpus luteum in the menstrual phase (Buse, Zöller, and van Esch 2008; Taketa et al 2018). Since corpora lutea may be missed on a histological section through the ovary, it is recommended to generate gross photographs of the ovaries before they are embedded in paraffin wax.…”
Section: How To Assess Female Fertility In Long-tailed Macaquesmentioning
confidence: 99%